Perceptions of teenagers on sexuality and sex education - Zocca, Adriana Rodrigues [UNESP]; Muzzeti, Luci Regina [UNESP]; Nogueira, Natalia Souza [UNESP]; Marcal Ribeiro, Paulo Rennes [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
Speaking of sexuality with teenagers is not always an easy task, but extremely necessary, as well as cross-cutting theme in education. This research aims to analyze the responses obtained with the application of a questionnaire to students of secondary education in public schools who attend Community pre-university preparatory course in the city of Matao / SP. The results showed that adolescents know the term sex education, but most of them never participated in projects on the subject. The doubts are related to the biological aspects and prevention. And the male feels comfortable talking about sexuality with friends and the females with their parents. Thus, we see the lack of contact with professionals in sexual education of these adolescents and the prevalence of biological speeches and disease prevention.
Keywords: Sexuality; Sex education; Adolescence